(untitled) (CIPEEX, 2025)
This report describes the experience carried out in the course Citizenship, Ethics, and Spirituality of the Administration program at Universidade Evangélica de Goiás – Campus Rubiataba, based on the analysis of the film “An Interview with God,” which addresses themes related to spirituality, ethics, and worldview. The objective of the activity was to promote deep reflection on fundamental issues, such as free will, suffering, life purpose, and the nature of God, and to understand how these principles can influence the formation of ethical, empathetic, and conscious leaders in both personal and professional spheres. The methodology employed included the screening of the film, followed by group analysis, identification of the main scenes and dialogues relevant to the proposed themes, presentation of reflections to the entire class, a collective debate, and the application of an interactive activity using the Kahoot application, articulating theoretical concepts of the course with individual experiences and everyday situations. During the activity, students discussed the importance of ethics, citizenship, and spirituality in personal, family, and professional life, enhancing skills such as active listening, organization of ideas, teamwork, and the application of ethical values in decision-making and leadership. The results indicated that participants developed greater awareness of how to integrate human and spiritual principles in professional contexts, strengthening group cohesion and promoting critical reflection on organizational challenges. It is concluded that this classroom activity significantly contributed to the academic, personal, and professional development of the students, highlighting the relevance of incorporating ethics, citizenship, and spirituality in the formation of administrators and in practicing a more humane, conscious, and committed leadership, demonstrating that ethical and spiritual values can positively transform both the work environment and society as a whole.